1965
DOI: 10.1246/bcsj.38.1015
|View full text |Cite
|
Sign up to set email alerts
|

Switch-over of the Mechanism of the Primary Processes in the Photo-oxidation of Xanthene Dyes as Revealed by the Oxygen Consumption Experiments

Abstract: The oxygen up-take of irradiated aqueous solutions of xanthene dyes has been investigated by means of Warburg’s apparatus, and evidence for a switch-over from a D–O to a D–D mechanism is obtained from the variation of dye-concentration. This view is supported by the photobleaching rate and the oxygen concentration effect at high eosine concentrations (∼10−4m). The quautum yields (γo2) of the consumption are estimated and it is found that γo2(D–D) is larger than γo2(D–O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

1974
1974
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 7 publications
1
25
1
Order By: Relevance
“…[33][34][35][36][37][38][39] Nevertheless, it is commonly accepted that in most cases, irreversible photodestruction is mediated via a transition from the excited singlet state S 1 to the excited triplet state T 1 (so called inter-system crossing, or ISC), which causes it to be reactive with surrounding molecules. 33,34,37,38 The key intermolecular interaction is between the triplet excited fluorophore and oxygen molecules as this can create oxygen radicals, which can then destroy the fluorophore.…”
Section: Photobleaching In Standard Conditionsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] Nevertheless, it is commonly accepted that in most cases, irreversible photodestruction is mediated via a transition from the excited singlet state S 1 to the excited triplet state T 1 (so called inter-system crossing, or ISC), which causes it to be reactive with surrounding molecules. 33,34,37,38 The key intermolecular interaction is between the triplet excited fluorophore and oxygen molecules as this can create oxygen radicals, which can then destroy the fluorophore.…”
Section: Photobleaching In Standard Conditionsmentioning
confidence: 99%
“…Most sensitisers have an optimum concentration for free radical generation in polymers, and this will depend on a number of factors including the frequency of side reactions due to clustering of the dye at higher concentrations. The photo-fading of xanthene dyes is known to be very sensitive to concentration and the dominant mechanism and kinetics both change at higher concentrations [27,28]. The effects of sensitiser concentration on PICL intensity are currently being examined in further studies on doped cast polymer films.…”
Section: Picl Emission From Wool Dyed With Xanthene Dyesmentioning
confidence: 99%
“…3 should depend on the kb2l oC C the kb22 N*2 so that the photobleaching rate kb2 with TPE cab be expressed as kb2 kb2l + kb22 =2fl1 N*+fl2 N*2 (5) where and /2 are parameters related to the fluorophore and environment.. Since N* j: (Denk et a!., 1990) for TPE, where P, is the excitation power, k,,1 and kb2 can be expressed as for D-P photobleaching kbl=al (6) kb2=2 P+a2J (7) where a1 and a2 are parameters determined by fl2 and the characteristics of excitation laser and fluorophores.…”
Section: The D-p Photobleaching Rate At Biological Imagingmentioning
confidence: 99%
“…The D-D and D-O photobleaching model proposed by Usui et al [6] could not elucidate commendably many photobleaching experimental results [7][8][9][10][11][12], and those results showed that the dependence of photobleaching rate on the probability of fluorophore molecules in excited states depended on the excitation way of One-or Two-Photon Excitation(OPE or TPE). Therefore, the extra excitation photons were considered to directly participate in the photobleaching event [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%